2014
DOI: 10.1161/circinterventions.113.000931
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Stent Apposition Causes High Shear Flow Disturbances and Delay in Neointimal Coverage as a Function of Strut to Wall Detachment Distance

Abstract: 13are common morphological findings in fatal cases of LST after DES.9-14 DES can interfere with this physiological healing process through different mechanisms: first, the antiproliferative drug released by the device prevents the cellular mitosis required to restore the endothelial continuity; second, the polymer carrying the drug exerts a proinflammatory effect itself 15 ; finally, in Background-Lack of re-endothelialization and neointimal coverage on stent struts has been put forward as the main underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 55 publications
11
120
0
Order By: Relevance
“…However, culprit lesions from patients with MI are severely diseased coronary vessel wall sites more prone to suboptimal apposition, 4,5 probably explanatory to our acute ISA findings. In previous OCT studies, 8,9,27,28 coverage of ISA struts has been found to be delayed when compared with well-apposed 8 found a 9× higher risk of incomplete coverage for ISA struts versus well-apposed struts. Our results are in line with these previous findings, as the improved strut coverage observed at 6-month follow-up in the OCT-guided group is interpreted caused by the better apposition of the stents at baseline.…”
Section: Downloaded From Oct Guidance and Stent Strut Coveragementioning
confidence: 86%
“…However, culprit lesions from patients with MI are severely diseased coronary vessel wall sites more prone to suboptimal apposition, 4,5 probably explanatory to our acute ISA findings. In previous OCT studies, 8,9,27,28 coverage of ISA struts has been found to be delayed when compared with well-apposed 8 found a 9× higher risk of incomplete coverage for ISA struts versus well-apposed struts. Our results are in line with these previous findings, as the improved strut coverage observed at 6-month follow-up in the OCT-guided group is interpreted caused by the better apposition of the stents at baseline.…”
Section: Downloaded From Oct Guidance and Stent Strut Coveragementioning
confidence: 86%
“…23 Of note, in vitro investigations directly assessing thrombogenicity could not confirm a correlation between the perpendicular ISA distance and clot mass volume. 24 In addition, the impact of ISA length or volume was not assessed in previous studies and should be assessed in future flow models or in vitro investigations to corroborate our in vivo findings.…”
Section: Malapposed Stent Strutsmentioning
confidence: 97%
“…Acute stent malapposition (ASM) is common at the time of stent implantation1, 2, 3, 4, 5, 6; however, it is still controversial whether ASM impacts long‐term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI). For example, Kimura et al7 reported that although most ASM after sirolimus‐eluting stent implantation did not resolve completely, the incidence of restenosis or thrombosis was not affected.…”
Section: Introductionmentioning
confidence: 99%